2005
DOI: 10.1080/09593332608618572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bromate Ions Level Introduced by Sodium Hypochlorite During Post-disinfection of Drinking Water

Abstract: During the last ten years, interest concerning the occurrence of bromate in drinking water has grown due to its potential carcinogenicity and the new regulations. One source of bromate in finished water is due to its presence in the sodium hypochlorite solutions used for the disinfection of water. In fact, the brine solutions used for the production of sodium hypochlorite contain bromide ions in varying degrees that subsequently generate a certain quantity of bromate ions. Bromate concentrations ranging from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
1
15
0
2
Order By: Relevance
“…Bromate, another disinfection byproduct, is found in some finished drinking waters as the result of ozonation disinfection processes [31]. Bromate in drinking water primarily is associated with the ozonation of water containing bromide and also has been reported as a contaminant in hypochlorite used for disinfection [32]. Bromate has been reported to be a carcinogen in mammalian studies [33] and there is significant interest in understanding bromate kinetics in blood [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Bromate, another disinfection byproduct, is found in some finished drinking waters as the result of ozonation disinfection processes [31]. Bromate in drinking water primarily is associated with the ozonation of water containing bromide and also has been reported as a contaminant in hypochlorite used for disinfection [32]. Bromate has been reported to be a carcinogen in mammalian studies [33] and there is significant interest in understanding bromate kinetics in blood [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that increased formation of brominated THMs occurs in chlorinated bromide rich waters (Hua et al, 2006;Ged & Boyer, 2014). Another factor associated with increased amount of brominated DBPs in swimming pool water is the use of sodium hypochlorite for water disinfection if the brine solution used for the production contain bromide ions (Bouland et al, 2005). The brominated THMs are in general more genotoxic and mutagenic compared to their chlorinated analogues (Kogevinas, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Despite differences in the original form of chlorine, the disinfection and chemical reaction characteristics of NaClO and Ca(ClO) 2 are generally similar to those of gaseous chlorine (Bryant et al 1992). A number of studies have shown significant levels of bromate in both hypochlorite feedstocks and treated waters in different countries-including the United Kingdom (Packham 1999), United States (Weinberg et al 2003), France (Bouland et al 2005), Japan (Asami et al 2009), andSpain (GarciaVillanova et al 2010)-using the hypochlorination disinfection method. In the Philippines, bromate was initially found at concentrations between 17 and 411 lg l -1 in tap drinking water samples using a simple ultraviolet (UV)-Vis spectrophotometric method (Espino and Cimatu 2003).…”
mentioning
confidence: 98%